2019
DOI: 10.3390/pharmaceutics11080408
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Magnetic Nanocarriers Drive Choline Kinase Alpha Inhibitor inside Cancer Cells for Combined Chemo-Hyperthermia Therapy

Abstract: Choline kinase α1 (ChoKα1) has become an excellent antitumor target. Among all the inhibitors synthetized, the new compound Ff35 shows an excellent capacity to inhibit ChoKα1 activity. However, soluble Ff35 is also capable of inhibiting choline uptake, making the inhibitor not selective for ChoKα1. In this study, we designed a new protocol with the aim of disentangling whether the Ff35 biological action is due to the inhibition of the enzyme and/or to the choline uptake. Moreover, we offer an alternative to av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
6
23
0
Order By: Relevance
“…Figure 7 A shows the cell viability compared to that of the untreated controls (CTRL-). As previously shown by our groups [ 20 , 22 , 30 , 42 ], BM are cytocompatible. Indeed, both M and DOXO-free 25 BM + 75 M nanoformulations display low cytotoxicity, and in all cases cell viability is above 80%, which is considered the cut-off indicated by ISO 10993–5:2009 [ 43 ].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Figure 7 A shows the cell viability compared to that of the untreated controls (CTRL-). As previously shown by our groups [ 20 , 22 , 30 , 42 ], BM are cytocompatible. Indeed, both M and DOXO-free 25 BM + 75 M nanoformulations display low cytotoxicity, and in all cases cell viability is above 80%, which is considered the cut-off indicated by ISO 10993–5:2009 [ 43 ].…”
Section: Resultssupporting
confidence: 74%
“…To determine the effect of magnetic hyperthermia on cell viability, in another set of experiments, HT-29 were incubated with the maximum concentration (300 µg/mL) of M, TBM, and the nanoassembly 25 TBM + 75 M for 24 h to allow the internalization of the nanoassemblies. After the incubation time, cells were exposed to AMF for 2 h. Finally, the viability was evaluated by the MTT colorimetric assay, as already described [ 30 ]. Briefly, 10 μL of the MTT 5 mg/mL in phosphate buffered saline (PBS) solution was added to the plate, incubated at 37 °C for 2 h, and supernatants were removed.…”
Section: Methodsmentioning
confidence: 99%
“…However, these MmsF-mediated magnetic nanoparticles are still not characterized enough to determine whether or not they could be of use in nanotechnology. On the contrary, MamC-mediated biomimetic nanoparticles (here referred as BMNPs) have demonstrated their potential as promising drug nanocarriers [5,6,14,15] and as hyperthermia agents [16,17], opening the possibility of a combined therapy by using the same nanoplatform. MamC controls magnetite nucleation and growth by both template and ionotropic effects [18], remaining attached to the nanoparticles and forming a nanocomposite (95 wt% magnetite + 5 wt% MamC) that results, not only in magnetic nanoparticles of different size and morphology (and thus magnetic properties) compared to those of chemically produced ones, but also in nanoparticles with novel surface properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a previous proof of concept showed that BMNPs were biocompatible and could be coupled with Oxaliplatin (Oxa) [14]. Therefore, these MamC-mediated BMNPs have been proposed as efficient nanocarriers [5,6,14,15] of a number of molecules offering crucial advantages over the use of inorganically synthesized magnetic nanoparticles to this end.…”
Section: Introductionmentioning
confidence: 99%
“…Active targeting can be achieved both by functionalization of the nanoparticle with probes against tumor-associated markers [ 15 , 19 , 20 ] or/and, as in the case of MNPs, by the application of a gradient magnetic field (GMF), usually a linear variation in the static magnetic field, which can enhance NP accumulation within the tumor [ 5 , 21 , 22 ]. Moreover, MNPs can also serve as magnetic hyperthermia (MH) agents, able to induce a local intratumor temperature increase—around 43–46 °C, which is effective against tumor cells—when exposed to an alternating magnetic field (AMF) [ 15 , 23 , 24 ]. Furthermore, MH also promotes the release or activation of therapeutic molecules coupled to the nanocarriers, thus locally increasing the concentration of the chemotherapeutic drug at the tumor site and prompting the effectiveness of the treatment [ 15 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%